A multiple stakeholder-based target-oriented robust optimization approach and its applications - Mangubat, Jivulter; Himang, Celbert; Solloso, Marlon; Alit, Dexter; Himang, Melanie; Mangubat, Milcah; Salumag, Patrobinson; Bongo, Miriam (Frontiers in Applied Mathematics and Statistics, 2026)
In real-world decision-making, multiple stakeholders often participate, each with diverse and sometimes conflicting interests, which may fall exclusively under the expertise of individual decision-makers. Existing multiple-criteria decision-making (MCDM) methods can accommodate multiple criteria but typically fail to reconcile conflicting stakeholder priorities into a satisficing solution. To address this gap, this paper proposes the multiple stakeholder-based target-oriented robust-optimization (MS-TORO) approach, which explicitly embeds stakeholder interests into an optimization framework that minimizes deviations among priorities. The implementation procedure involves eliciting ordinal stakeholder preferences, parameterizing trade-offs, and solving the optimization model to generate an aggregated solution. Three case studies demonstrate the applicability and viability of MS-TORO, showing that it effectively produces solutions that satisfy the performance targets defined by each decision-maker across all criteria.